2014
DOI: 10.1002/pds.3726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of clinical codes to identify cataract and glaucoma in the UK Clinical Practice Research Datalink

Abstract: High PPV suggests that the algorithms based on the clinical Read codes are sufficient to identify the cataract and glaucoma cases in CPRD. However, these codes alone may not be able to accurately identify the timing of the diagnosis of these eye disorders. Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…by requesting additional data from GPs for a subset of patients), results for the SA did not find differences between the algorithms with intermediate (2) and least sensitivity (3). Similar findings have been reported in other studies using CPRD data to identify different conditions, [100][101][102] which suggests that CPRD Read Codes can be used to identify a representative sample of patients with a particular condition in the UK. Our study was conducted and reported in accordance with recent guidelines for studies conducted using observational routinely collected health data (REporting of studies Conducted using Observational Routinely collected health Data, RECORD guidelines 103 ), which recognise the additional challenges of conducting research using routinely collected data obtained for administrative and clinical purposes rather than research.…”
Section: Systematic Review and Meta-analysissupporting
confidence: 87%
See 1 more Smart Citation
“…by requesting additional data from GPs for a subset of patients), results for the SA did not find differences between the algorithms with intermediate (2) and least sensitivity (3). Similar findings have been reported in other studies using CPRD data to identify different conditions, [100][101][102] which suggests that CPRD Read Codes can be used to identify a representative sample of patients with a particular condition in the UK. Our study was conducted and reported in accordance with recent guidelines for studies conducted using observational routinely collected health data (REporting of studies Conducted using Observational Routinely collected health Data, RECORD guidelines 103 ), which recognise the additional challenges of conducting research using routinely collected data obtained for administrative and clinical purposes rather than research.…”
Section: Systematic Review and Meta-analysissupporting
confidence: 87%
“…In addition, a proportion of patients did not have sufficient observation time in the cohort study for the algorithm to discriminate between BNP tested and BNP monitored. Ideally, we should have conducted a validation study (sending questionnaires to GPs for a sample of the cohort to verify the diagnosis and the timing of the diagnosis) 100 on the exposure algorithm but this was difficult given the lack of consensus about what BNP monitoring should constitute and the limited time frame of the project.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…Data source and population for pharmacoepidemiological studies Data were extracted from the UK Clinical Practice Research Datalink (CPRD) which contains electronic medical record (EMR) data from >5 million UK people (further details of the data source are contained in online supplement 1) [10][11][12]. People with medically treated asthma and ocular hypertension were identified by Read Codes and prescriptions for asthma and ocular hypertension medicines.…”
Section: Methodsmentioning
confidence: 99%
“…3 Thus, to determine the accuracy of AS diagnostic codes, we administered a questionnaire to the GPs caring for patients with one or more AS diagnoses (Read code N100.00, “Ankylosing spondylitis”) in THIN. 67 This method was selected for AS diagnosis validation because of the potential for diagnoses to be miscoded in GP records, such as in the event that a tentative diagnosis was recorded using a code that failed to capture the diagnostic uncertainty.…”
Section: Methodsmentioning
confidence: 99%